(untitled) (Fiep Bulletin - online, 2014)
Outdoor training is the central issue and it´s briefly rated as a kind of training applied to employees of certain companies outside the workplace through adventure sports. It has been practiced for a long time for companies spread throughout the world and has brought good results for the performance of the people who are involved in it. Despite its study be widely encouraged by the universities throughout the world, the outdoor training is not yet commented nor practiced with the same strength in Brazil, either in business or in colleges and schools. Therefore, this work was based in a bibliographic survey methodology, application of research through questionnaires and exploratory and descriptive analysis of the data, and with the primary aim of presenting a kind of training, which combined with the area sports highlights skills and initiatives replicable practices of business, and confirm how much it is still little used in Brazil showing the results of applied research from the students of Post-Graduate (latu sense) in Ribeirao Preto-SP.